Poverty, by America [large type] - Desmond, Matthew (Random House Large Print, 2023)
"The United States, the richest country on earth, has more poverty than any other advanced democracy. Why? Why does this land of plenty allow one in every eight of its children to go without basic necessities, permit scores of its citizens to live and die on the streets, and authorize its corporations to pay poverty wages? In this landmark book, acclaimed sociologist Matthew Desmond draws on history, research, and original reporting to show how affluent Americans knowingly and unknowingly keep poor people poor"--